The Exploration of a Multi-Theoretical Framework for Holistic and Democratic Adult ESL Instruction - Fujuan Tan; Lee Nabb (Adult Education Research Conference, 2015)
This paper explores a multi-theoretical framework that capitalizes on the use of students’ prior experiences in practicing culturally responsive education among adult English as a Second Language (ESL) learners, with an aim to promote language proficiency, socio-cultural competence, and personal growth, and therefore to facilitate holistic and democratic instruction.
Keywords: adult ESL; multi-theoretical; prior experience; democratic instruction